2011
DOI: 10.1038/mt.2010.283
|View full text |Cite
|
Sign up to set email alerts
|

Expressed Cell-penetrating Peptides Can Induce a Bystander Effect, but Passage Through the Secretory Pathway Reduces Protein Transduction Activity

Abstract: Despite advances in vector technology, inefficient gene transfer still limits clinical efficacy of cancer gene therapy. Cell-penetrating peptides (CPPs), such as the basic domain of the transactivator of transcription (Tat) protein of HIV-1, are internalized by intact cells and have been used to deliver purified recombinant proteins. A combination of gene therapy with protein transduction technology could induce a strong bystander effect and represent a platform to deliver proteins to target cells. However, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…on biological activities other than transport) have been previously cataloged in a recent review [ 2 ] and include a variety of biological effects, such as oxidative stress effects, responsiveness to heparan sulfate, lipid remodeling, and actin rearrangement. Interestingly, the only prior study that has addressed the interaction of CPPs with proprotein convertases concluded that furin may act to inactivate the TAT 7-57 peptide, although furin-mediated inactivation was not directly demonstrated in this work [ 51 ]. Our data support a contradictory conclusion: that TAT4 7-57 acts to inhibit intracellular furin and/or other convertases.…”
Section: Discussionmentioning
confidence: 90%
“…on biological activities other than transport) have been previously cataloged in a recent review [ 2 ] and include a variety of biological effects, such as oxidative stress effects, responsiveness to heparan sulfate, lipid remodeling, and actin rearrangement. Interestingly, the only prior study that has addressed the interaction of CPPs with proprotein convertases concluded that furin may act to inactivate the TAT 7-57 peptide, although furin-mediated inactivation was not directly demonstrated in this work [ 51 ]. Our data support a contradictory conclusion: that TAT4 7-57 acts to inhibit intracellular furin and/or other convertases.…”
Section: Discussionmentioning
confidence: 90%
“…Secretion of PTD‐containing molecules has been the goal of several research papers (2327). However, as these studies unanimously demonstrate, and our initial experiments show, attachment of a PTD domain to a molecule targeted for secretion (such as mouse IgG2a Fc domain) has a dramatic inhibitory effect on their secretion with most (or all) of the protein retained inside the producing cell.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the EGFP partner functions as a secretion carrier. In another recent study, the fluorescent mCherry protein was also efficiently secreted when linked to the TAT3 sequence (27). The disadvantage of these strategies is that fluorescent proteins are foreign and therefore immunogenic in vivo (29), and as such are not suitable for clinical use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TAT peptide sequence GRKKRRQRRRPPQ is, however, easily cleaved by furin. Thus, CPP is not stable enough in vivo for efficient cargo delivery [ 96 ]. Hemmati et al [ 97 ] identified 310 decapeptides with predicted CPP activity in the proteome of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).…”
Section: Under-appreciated Versatility Of Penetratinsmentioning
confidence: 99%